2015
DOI: 10.1002/2015jg003108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of plant competition on the coupling between vegetation and the atmosphere

Abstract: Competition between plants for resources is an important selective force. As a result competition through natural selection determines vegetation functioning and associated atmospheric interactions. Our aim was to investigate how the coupling between vegetation and atmosphere is influenced by plant competition. Though included in some coupled vegetation-atmosphere models, little attention has been paid to systematically study the impact of plant competition in determining the evolution of surface and atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For instance, using this approach it was shown that EGT models realistically predicted elevated CO 2 effects on crop structure and functioning (including atmospheric feedback) as found in field-applied elevated CO 2 experiments [52,53].…”
Section: Make Crop-specific Egt Modelsmentioning
confidence: 95%
“…For instance, using this approach it was shown that EGT models realistically predicted elevated CO 2 effects on crop structure and functioning (including atmospheric feedback) as found in field-applied elevated CO 2 experiments [52,53].…”
Section: Make Crop-specific Egt Modelsmentioning
confidence: 95%
“…Examples are uncertainties related to the development in canopy structure (e.g., increase in leaf area index; Anten et al, 2004) or leaf thickness and nitrogen allocation (Bezemer et al, 1998). Furthermore, when genotypic responses of plants to climate change are considered, the vegetation distribution might be affected through natural selection (Van Loon et al, 2015). As most plant species respond differently to atmospheric perturbations, regional or even continental changes in the surface energy balance might occur that have a strong effect on the land-atmosphere interactions.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…For example, game theoretical models predicted that selection might favour plants with more leaf area or that grow taller than would be needed for maximized production (Anten, 2002;Falster and Westoby, 2003). In addition, a game theoretical model, which assumed that the best competitors will prevail under elevated [CO 2 ], gave better predictions of measured LAI and photosynthesis and net ecosystem productivity in elevated [CO 2 ] experiments than models that assume that plants with the inherent highest photosynthesis will prevail (Van Loon et al, 2014, 2015. Together with the findings reported here, this also suggests that competition strongly mediates plant adaptations to elevated [CO 2 ] and this may have important consequences for future species distribution and vegetation functioning.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study that included competition through natural selection (i.e. game theoretical principles) accurately predicted the LAI, net photosynthesis and stomatal conductance of soybean stands grown at elevated [CO 2 ] obtained in free air carbon dioxide enrichment (FACE) experiments, and this prediction was much better than a model that did not consider these interactions (Van Loon et al, 2014, 2015. However, the role of plant-plant interactions in mediating vegetation responses to elevated [CO 2 ] is still poorly understood (Bazzaz and McConnaughay, 1992;Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%